ANALISIS PENGGUNAAN PESAWAT TANPA AWAK (DRONE) DALAM KEBIJAKAN KONTRATERORISME AMERIKA SERIKAT DI PAKISTAN PASCA 9/11 - Anjani, Indira; Susetianingsih, Hermini; Pattipeilohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
As a part of counterterrorism tool, the CIA’s armed drone was firstseen attack Al Qaeda in Pakistan on 2004. Some of criticism fromhumanitarian organization claimed that the attacks are inhumane,violate the international law and constitute a war crime. However, theUS government denied and contending that the drone attackscomplied with all applicable law, including the laws of war and thatthe method of attack is effective. This research attempts to explicatehow the US drone attacks in Pakistan and It also analyzes the factorsthat encourage the US to keep using drones as a weapon in counterterrorismin Pakistan despite the fact that the drone attacks havecaused the deaths of civilians in Pakistan.